Women under the Panchayat Regime: Parijat’s Under the Sleepless Mountain as a Feminist Project - Gautam, Mani Bhadra (SCHOLARS: Journal of Arts & Humanities, 2024)
The representation of the female in Nepali fiction has been a fascinating subject for critics. This paper examines the representational position of the women as projected in Parijat’s Under the Sleepless Mountain. In this novel, the novelist critiques the patriarchal society’s treatment to women in a different social structure. Parijat’s female characters are projected as suffering and marginalized people of the Nepali society around the student’s revolution of the early 1980s. Other issues raised in this paper focus on students and subaltern characters who are treated badly as they raise voice against the oppressive Panchayat system and other kinds of dominance. She writes against social wrongs and ill intended human activities. She exposes the character’s desire for freedom, individuality and equal rights. Thus, the objective of this study is to find out the answers to whether the suffering of women, laborers and students are concretely represented in her novel or not. In this paper, this researcher explores the issues around the plight of the female, which are interpreted from the feminist perspective. The relevant feminist notions developed by the feminist critics such as Sidonie Smith, Julia Watson, Catherine Belsey and Susan Bassnett have been adopted for textual analysis as a methodological tool. This paper concludes that the gender discrimination and political disharmony are the major obstacles to women upliftment.